Pengaruh Financial Technology Terhadap Financial Satisfaction Pada UMKM Di Kota Jambi Dengan Disruptive Technology Sebagai Variabel Mediasi - Enjanita, Sanci; Lubis, Tona Aurora; Indrawijaya, Sigit (Dinasti Review Publisher, 2024)
Financial Technology (FinTech) and Micro, Small, and Medium Enterprises (MSMEs) exhibit several important dynamics within the financial ecosystem and business development. FinTech has had a significant impact on MSMEs, especially in terms of access to financial services that were previously difficult for this sector to reach, including enhancing financial satisfaction. This study aims to analyze the influence of Financial Technology on Financial Satisfaction in MSMEs in Jambi City, with Disruptive Technology as a mediating variable. This research is quantitative and analyzed using SEM PLS. The study population consists of MSME owners in Jambi City. The study concludes as follows: Financial Technology has a direct impact on Financial Satisfaction. Good Financial Technology will improve Financial Satisfaction. Similarly, Disruptive Technology can enhance Financial Satisfaction. Disruptive Technology as a mediating factor can enhance the influence of Financial Technology on Financial Satisfaction in MSMEs in Jambi City.